2015
DOI: 10.1590/0074-02760140410
|View full text |Cite
|
Sign up to set email alerts
|

Congenital transmission of Trypanosoma cruzi in central Brazil. A study of 1,211 individuals born to infected mothers

Abstract: Transmission of Trypanosoma cruzi during pregnancy is estimated to occur in less than 20% of infected mothers; however, the etiopathogenesis is not completely understood. The Centre for Studies on Chagas Disease provides confirmation of T. cruzi infection for individuals living in central Brazil. In this retrospective hospital-based study, all requests for diagnosis of T. cruzi infection in individuals less than 21 years old from 1994-2014 were searched. We end with 1,211 individuals and their respective infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
24

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 14 publications
0
30
0
24
Order By: Relevance
“…This suggests that the presence of TcII in the study area may be associated with lower rates of transmission than TcV, which predominates in the southern regions of Brazil and other Southern Cone countries, where the vertical transmission rates are generally known (108) . Despite existing scientific evidence, important gaps remain in terms of the role of genetic diversity of T. cruzi in relation to the evolution of the chronic phase of the disease, the risk of congenital transmission or reactivation, and the occurrence of oral outbreaks transmission (27) .…”
Section: Vertical Transmission (Congenital)mentioning
confidence: 86%
“…This suggests that the presence of TcII in the study area may be associated with lower rates of transmission than TcV, which predominates in the southern regions of Brazil and other Southern Cone countries, where the vertical transmission rates are generally known (108) . Despite existing scientific evidence, important gaps remain in terms of the role of genetic diversity of T. cruzi in relation to the evolution of the chronic phase of the disease, the risk of congenital transmission or reactivation, and the occurrence of oral outbreaks transmission (27) .…”
Section: Vertical Transmission (Congenital)mentioning
confidence: 86%
“…Parasitemia clearly fluctuates because PCR analysis is not consistently positive or negative in individuals over time [10]. T. cruzi can also cross the placenta leading to congenital transmission in ~5% of cases, with some geographic variability linked to T. cruzi genotype [79]. As outlined below, parasites have been detected in a wide of range of other organs, but whether any of these sites serve as genuine long-term reservoirs, or simply become transiently infected is far from clear.…”
Section: Elusively Reclusive: T Cruzi In the Chronic Phasementioning
confidence: 99%
“…9 It has been suggested that the congenital transmission rate might vary according to the parasite's genotype, but available data are inconclusive. [10][11][12][13] Trypanosoma cruzi genotypes have been grouped into discrete typing units (DTUs), with TcI being assumed to be more frequent in Mexico and Central America and non-TcI (TcII-VI) being dominant in the Southern Cone region of South America. 14,15 However, recent studies suggest that TcI might not be predominant in all regions of Mexico.…”
Section: Introductionmentioning
confidence: 99%